Hybrid superhydrophilic–superhydrophobic micro/nanostructures fabricated by femtosecond laser-induced forward transfer for sub-femtomolar Raman detection - Ma, Xiaodan (Microsyst Nanoeng, 2019)
Raman spectroscopy plays a crucial role in biochemical analysis. Recently, superhydrophobic surface-enhanced Raman scattering (SERS) substrates have enhanced detection limits by concentrating target molecules into small areas. However, due to the wet transition phenomenon, further reduction of the droplet contact area is prevented, and the detection limit is restricted. This paper proposes a simple method involving femtosecond laser-induced forward transfer for preparing a hybrid superhydrophilic–superhydrophobic SERS (HS-SERS) substrate by introducing a superhydrophilic pattern to promote the target molecules to concentrate on it for ultratrace detection. Furthermore, the HS-SERS substrate is heated to promote a smaller concentrated area. The water vapor film formed by the contact of the solution with the substrate overcomes droplet collapse, and the target molecules are completely concentrated into the superhydrophilic region without loss during evaporation. Finally, the concentrated region is successfully reduced, and the detection limit is enhanced. The HS-SERS substrate achieved a final contact area of 0.013 mm(2), a 12.1-fold decrease from the unheated case. The reduction of the contact area led to a detection limit concentration as low as 10(−16) M for a Rhodamine 6G solution. In addition, the HS-SERS substrate accurately controlled the size of the concentrated areas through the superhydrophilic pattern, which can be attributed to the favorable repeatability of the droplet concentration results. In addition, the preparation method is flexible and has the potential for fluid mixing, fluid transport, and biochemical sensors, etc.